2015
DOI: 10.1021/acs.chemmater.5b03266
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Intermolecular Interactions in Organic Electronic Materials: Implications for the Molecular Packing vs Electronic Properties of Acenes

Abstract: Noncovalent intermolecular interactions, which can be tuned through the toolbox of synthetic chemistry, determine not only the molecular packing but also the resulting electronic, optical, and mechanical properties of materials derived from π-conjugated molecules, oligomers, and polymers. Here, we provide an overview of the theoretical underpinnings of noncovalent intermolecular interactions and briefly discuss the computational chemistry approaches used to understand the magnitude of these interactions. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
198
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(207 citation statements)
references
References 207 publications
6
198
0
3
Order By: Relevance
“…Overall, the present study explores the new approacht owards controlling the optical behaviour of functional dyes in the solid state, throughm anipulation of the structure of saturated rings rather than the nature of aliphatic chains. [33] Experimental Section…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the present study explores the new approacht owards controlling the optical behaviour of functional dyes in the solid state, throughm anipulation of the structure of saturated rings rather than the nature of aliphatic chains. [33] Experimental Section…”
Section: Resultsmentioning
confidence: 99%
“…[67,68] For example, fluorophobic interactions from fluoroalkyl chains often induce unique self-organized architectures and to facilitate charge transport properties. [67,68] For example, fluorophobic interactions from fluoroalkyl chains often induce unique self-organized architectures and to facilitate charge transport properties.…”
Section: Reviewmentioning
confidence: 99%
“…[22,[34][35][36][37][38][39][40][41][42][43][44][45][46]). Specifically, Ambrosch-Draxl et al [22] have suggested that a combination of dispersion-inclusive DFT methods, which they found to predict lattice parameters in agreement with experiments for acene crystals, followed by MBPT calculations can be used to explore quantitative differences in optical properties of pentacene polymorphs.…”
Section: Introductionmentioning
confidence: 99%